Non-invasive quantification of aortic regurgitation by Doppler echocardiography. Issue 2 (February 1983) - Diebold, B; Peronneau, P; Blanchard, D; Colonna, G; Guermonprez, J L; Forman, J; Sellier, P; Maurice, P
Abstract : This study was undertaken to assess the contribution of Doppler echocardiography to the quantification of aortic valve regurgitation. Ultrasound examination was performed by recording aortic arch blood flow from the suprasternal notch. A non-invasive index of valve regurgitation was obtained by calculating the ratio between the maximal amplitude of forward flow during systole and the amplitude of retrograde flow during diastole measured at the onset of the R wave of the electrocardiogram. This index was compared with semiquantitative data derived from supravalvular aortography in 93 patients. In pure aortic regurgitation (67 patients) the results showed a high correlation coefficient between Doppler and angiographic estimates. In cases of associated aortic valve stenosis there were problems in the accurate estimation of systolic blood flow which led to global overestimation in general of the degree of regurgitation and considerable lack of precision in individual patients. But in general Doppler echocardiography appeared to be a successful technique to quantify pure aortic regurgitation.